2017 Workshop on Research, Education and Development of Unmanned Aerial Systems (RED-UAS) 2017
DOI: 10.1109/red-uas.2017.8101638
|View full text |Cite
|
Sign up to set email alerts
|

Optimal path of a UAV engaged in wind-influenced circular towing

Abstract: Abstract-This paper considers the dynamic optimization of the planned path for an Unmanned Aerial Vehicle (UAV) engaged in circular towing of a cable-body system, such that the motion of the towed endmass is stabilized with minimum motion relative to a desired target position. The ultimate research objective is to develop a concept to enable a fixed wing UAV to be used for end body precision positioning maneuvers such as object pickup/dropoff in order to extend the possible range for this type of missions. Whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…However, as can be seen in Figure 10 for each one of the main application scopes, a different propulsion method was most often used. There are, however, exceptions to this statement; for instance, the load transportation scope was dominated by the usage of multirotor tUAVs, but some publications explored the application of fixed-wing aircraft [22,[34][35][36] and even helicopters [26] as a viable solution.…”
Section: Discussionmentioning
confidence: 99%
“…However, as can be seen in Figure 10 for each one of the main application scopes, a different propulsion method was most often used. There are, however, exceptions to this statement; for instance, the load transportation scope was dominated by the usage of multirotor tUAVs, but some publications explored the application of fixed-wing aircraft [22,[34][35][36] and even helicopters [26] as a viable solution.…”
Section: Discussionmentioning
confidence: 99%
“…In Ref. [20], the authors found that the optimal vertical path in steady winds can be approximated using a cosine function:…”
Section: Path Control Strategy To Reduce Vertical Oscillations In Windsmentioning
confidence: 99%
“…In order to have optimal path planning and UAV range estimates, it is necessary to have air data information [10,24]. In addition, having air data knowledge, can open up for more complex maneuvers such as high precision deep-stall landings [20], precision object delivery [19,21], or for detecting critical performance degradation caused by ice accretion on the UAV due to atmospheric icing conditions [32].…”
Section: Introductionmentioning
confidence: 99%